2017
DOI: 10.1186/s13104-017-2543-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of modern contraceptive practice in Yaoundé-Cameroon: a community based cross sectional study

Abstract: Background: Despite numerous efforts put in place to increase modern contraceptive use in Cameroon as a means to fight maternal and infant mortality, the prevalence of modern contraception has shown only a slow increase and maternal mortality is constantly rising. This paper attempts to identify barriers to contraceptive use in Biyem-Assi, Yaoundé-Cameroon so as to clearly define in which domain and how to intervene concerning contraceptive use in Cameroon.Methods: It was a community-based cross sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 10 publications
6
24
0
Order By: Relevance
“…The current result was also consistent with the results of two cross-sectional studies done in Northwest and Western Ethiopia where reproductive age women aged 35-49 years and > 44 years respectively were less likely utilized modern contraceptive method [10,14]. Another cross-sectional study done in Cameroon in 2014 and 2015 also showed that age > 30 years was negatively associated with modern contraceptive method utilization which was also consistent with the current study [8]. This might be due to the reason that reproductive-age women from low-income countries become more economically stable at their late reproductive age and might not want to utilize contraceptive methods to bear more children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current result was also consistent with the results of two cross-sectional studies done in Northwest and Western Ethiopia where reproductive age women aged 35-49 years and > 44 years respectively were less likely utilized modern contraceptive method [10,14]. Another cross-sectional study done in Cameroon in 2014 and 2015 also showed that age > 30 years was negatively associated with modern contraceptive method utilization which was also consistent with the current study [8]. This might be due to the reason that reproductive-age women from low-income countries become more economically stable at their late reproductive age and might not want to utilize contraceptive methods to bear more children.…”
Section: Discussionsupporting
confidence: 91%
“…To the contradict, another study was done in the same country (Ghana) showed a prevalence of only 21% [7]. A community-based crosssectional study done on reproductive-age women in Yaoundé-Cameroon showed that 58.9% used a modern contraceptive method [8]. Different studies done in Ethiopia [9][10][11][12][13][14] showed extremely variable results in the prevalence of modern contraceptive use which ranged from 20.8% from the study done at Bale Zone, South East Ethiopia [9] to 71.9% from the community-based cross-sectional study done at western Ethiopia [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that there is a shift of values in the society in Indonesia, but this assumption must be proved through further qualitative research. The same results were shown by studies in Bangladesh and Cameroon [36][37][38]. However, the studies in North Ethiopia and Malawi showed that education contributes significantly to the use of overall contraception method [39,40].…”
Section: Discussionsupporting
confidence: 74%
“…One study from Cameroun [ 12 ] revealed that the husband’s approval of contraception and discussion about FP within the couple had a protective relationship with unmet need. A study from Rwanda [ 13 ] went on explaining that unmet need was higher among women who did not approve FP, those who believed their partner did not approve FP or who did not know his attitude and those who had never discussed FP with their partners or had done so, rarely.…”
Section: Introductionmentioning
confidence: 99%